Penanda Genetik Tarsius (Tarsius spp.) dengan Menggunakan Gen Cytochrome Oxidase I (COI) DNA Mitokondria (mtDNA) Melalui Metode Sekuensing - ,, Wirdateti; Wulandari, Sri Wijayanti; Kuswandi, Paramita Cahyaningrum (Perhimpunan Biologi Indonesia, 2015)
ABSTRACTTarsier (Tarsius spp.) are the smallest primates in the world. Currently there are 10 species, of which 9 species are distributed in Indonesia and 8 species of them are endemic to Sulawesi. Morphologically the Sulawesi spesies are almost similar. This research is aimed to identify the use of Cytochrome Oxidase I (COI) gene as a genetic marker on Tarsius spp. for conservation purposes. Sixteen individuals consisted of 10 Tarsius bancanus, 4 Tarsius sp., 1 Tarsius wallacei , and 1 Tarsius sangirensis were collected from various places and analysed using COI gene. The results showed there were 238 different sites of nucleotides and 159 sites of amino acids from the total amount of 838 bp. The genetic distance by Kimura-2 parameter showed the highest value was 26% while the lowest was 0%. The average genetic distance was 11,5%. Phylogenetic tree constructed by Neighbour-Joining method based on nucleotides sequence showed that the COI gene could be used as a genetic marker to differentiate among Tarsius spp. but could not be used as a clear marker for tarsiers in Sulawesi. Based on the analysis, there is a high value of genetic variation among Tarsius spp. with much lower genetic variation in Western Tarsier population compared to Eastern Tarsier. Keyword: Genetic marker, tarsier, COI, DNA mitochondria, conservation